Crossrail Project : infrastructure design and construction. Volume 3 - Black, Mike (Engineering geologist) (ICE Publishing, 2016)
This volume contains a collection of 34 papers submitted to Crossrail's Technical Papers Competition between 2014 and 2015. Contributions have come from consultants, contractors, suppliers and third-party stakeholders involved in design and construction across the Crossrail project.